An exploration of how Generation Y demographics and point of sale marketing methods affect Generation Y’s purchasing decisions in bars - Hastings, William R. (Kansas State University, 2012)
Alcoholic beverages and on premise alcoholic beverage retailers have become important to the food and beverage industry in the past three millennia. On premise consumption of alcoholic beverages is necessary for income in bars which makes it crucial for alcoholic beverage producers and retailers to identify methods to increase sales and consumption of their products. One method used by retailers and producers is to market their product at the point of sale (POS). However, the effectiveness of various POS marketing methods can vary depending on the demographics of the consumer cohort being targeted. The Generation Y cohort is reaching legal drinking age and is quickly becoming the majority of customers patronizing bars. Because many members of Generation Y are new to the drinking and bar scene, point of sale marketing may be an effective method of introducing Generation Y to high profit beverages. Currently, 33% of all alcohol beverage marketing expenditures target customers at the point of sale. Therefore, the purpose of this study was to investigate how components of on-premise marketing methods, along with demographics, influence Generation Y’s purchasing decisions in bars. The sample was 216 members of Generation Y from across the country. Instrument development included a review of literature, three focus groups, a pilot study and a review by three industry experts. The final survey was distributed nationwide by Zoomerang.com. T-tests, ANOVA, factor analysis, and regression were used for data analysis. Results indicated that respondents patronized local bars and usually once a week, they drank regular beer, and spent an average of $23 per outing. Males, non-whites, and those who patronize bars on a weekly basis were significantly more likely to purchase alcoholic beverages based on POS logoed items at a bar. However, most respondents indicated that POS logoed items had no impact on their decisions and that assurance marketing was more important. Future studies need to be conducted focusing on either assurance marketing or logoed items. Also, demographic specific studies could be useful for local bars.
Keywords: Point of Sale Marketing; Bars; Generation Y; Marketing (0338)